The Impact of Social Media, Price, and Product Quality on Purchasing Decisions on Whitening Skin Care Products - Datu, Daniela Elim Aprilina (Advances: Jurnal Ekonomi & Bisnis, 2023)
Purpose: This study aims to determine the influence of social media variables, price, and product quality on purchasing decisions on scarlet whitening skin care products, both partially and simultaneously. Research Design and Methodology: This study used quantitative methods. Purposive sampling determined 50 respondents. Data was collected by distributing questionnaires and samples to all Scarlett whitening skin care product buyers. Using a Likert scale, respondents' answers were processed by multiple regression analysis, t-test, F test, and R2 test. Findings and Discussion: The results of t or partial test studies show that social media positively and significantly affects purchasing decisions. Price and product quality have a positive but insignificant effect on buying decisions. Simultaneously, social media, price, and product quality positively influence purchasing decisions. Implications: Research variables have limitations. This study tested only four research variables: social media, price, product quality, and purchasing decisions. Furthermore, it is expected that additional variables may also affect many things in this study because there are still many other variables that can affect buying decisions that are not used in this study, causing what the author studied to be far from perfect. The sample in this study included only 50 respondents, so the results could not represent the entire number of users of Scarlett's whitening skin care products. In subsequent studies, it is recommended to take more samples, which will improve the accuracy of the data.